Review article: Becoming and being coeliac—special considerations for childhood, adolescence and beyond. (11th July 2022) - Chang, Denis; O'Shea, Delia; Therrien, Amelie; Silvester, Jocelyn A.
Abstract : Classically considered a disease of early childhood characterised by malabsorption and failure to thrive, coeliac disease is now recognised to arise in genetically susceptible individuals at any age. Although permissive HLA genotypes are the strongest predictor of coeliac disease, they are not sufficient. Several prospective cohort studies enrolling genetically at‐risk infants have investigated the role of potential triggers of coeliac disease autoimmunity, such as timing of gluten introduction, viral infections and dietary patterns. Much less is known about triggers of coeliac disease in adulthood. Better understanding of factors leading to coeliac disease may be helpful in the management of those with potential coeliac disease (elevated serum celiac antibodies without villous atrophy in the small intestine), many of whom initiate a gluten‐free diet without demonstration of villous atrophy. There are a range of clinical presentations of celiac disease in childhood and patterns of coeliac serology, including fluctuation and spontaneous reversion on a gluten‐containing diet, vary. There is a current debate over best strategies to manage adults and children with potential coeliac disease to avoid over‐treatment and under‐treatment. Childhood and adolescence carry unique issues pertaining to the diagnosis and management of coeliac disease, and include nutrition and growth, rescreening, repeat biopsy, dietary adherence concerns and transition to adult care. In conclusion, while coeliac disease has similar pathogenesis and general clinical manifestations in paediatric and adult populations, diagnostic and management approaches need to adapt to the developmental stages.